Venous Thromboembolism in COVID-19 - Schulman, Sam; Hu, Yu; Konstantinides, Stavros (Thrombosis and Haemostasis, 2020)
The coronavirus disease 2019 (COVID-19) is our latest pandemic, preceded by the H1N1 swine flu in 2009, which lasted approximately 19 months. One of the special characteristics of COVID-19 is the propensity to cause venous thromboembolism (VTE). Thromboinflammation seems to play a prominent role in the pathogenesis. We will here review some mechanisms in the pathogenesis and discuss some hematological biomarkers, and also whether they serve as useful risk factors for VTE. The role of general risk assessment models for medically ill patients specifically in COVID-19 is appraised. The type of prophylaxis and particularly whether standard or augmented doses of chemoprophylaxis should be used is reviewed based on available evidence. We are also comparing recommendations from 10 different guidance or position/consensus statements. Treatment recommendations for patients with COVID-19 and pulmonary embolism are discussed with current general treatment guidelines as reference. Specifics for patients with COVID-19 are pointed out and the potential role of thrombolytic treatment is explored.
Keywords: COVID-19; D-dimer; risk assessment models; venous thromboembolism; prophylaxis; treatment